A virtual ad hoc network testbed. (6th July 2010) - Poylisher, Alex; Serban, Constantin; Lee, John; Lu, Tai-Chuan; Chadha, Ritu; Chiang, Cho-Yu; Orlando, Robert; Jakubowski, Kimberly
Testing of applications for ad hoc networks poses a special technical challenge due to the difficulty of conducting experiments in an ad hoc network environment at a scale larger than a few nodes. One approach is to conduct experiments in a testbed that can imitate an ad hoc network. This requires the development of technologies that enable multiple instances of unmodified application software on a set of hosts to communicate via a simulated network that behaves like a real ad hoc network. In this paper, we describe the testbed developed under the virtual ad hoc network (VAN) testbed project for testing applications over ad hoc networks, with a special focus on network management applications. The testbed employs Xen-based virtualisation to achieve resource scalability. The infrastructure for the testbed provides an integrated platform consisting of virtual nodes running the actual software under test, augmented with a simulated network environment. Our goal is to enable software testing over large-scale (500-1000 nodes) ad hoc networks using the VAN testbed.